Severiano Mario Porto's projects in the north of Brazil : a bioclimatic research about the Amazon architecture - Medeiros, Ayana Dantas de (2020)
The architect Severiano Mário Porto is a Brazilian icon. In Amazon region, his projects outstanding characteristics show the local climate potential, bioclimatic strategies, flexible design, cost optimization, renewable materials and regional labour techniques. This paper aims to present the results of an investigation to catalogue the bioclimatic strategies used Severiano Mario Porto design in Boa Vista buildings, focusing on daylighting, shading and ventilation strategies, also evaluated with user’s perspective. The method includes documentary survey and case studies selection, the use of morphological diagrams, on-site monitoring, user feedback and computational analysis. The results identify 14 buildings and 4 from these were selected as case studies. Morphological diagrams demonstrate mixed solutions for design, resulting in an expressiveness work for treatment of local impasses. On site monitoring reveals problems related with low illuminance levels and some minimum view quality, due to solar protection elements. The users' opinion demonstrate satisfaction with the luminous environment, although it is always necessary to have artificial lights on. The results of lighting computer simulations, however, shows that the original project have good daylighting levels, before interventions like solar controls glazing with low transmittance. The main strategies used by the architect were… Crossing data, it is possible to conclude that the original projects of Severiano Mário Porto in Boa Vista present good quality in terms of daylighting and shading but, in practice, wasted by inadequate interventions.